(untitled) (Journal of Universal Science Research, 2025)
This article is devoted to the importance of literary translation in intercultural communication, particularly, providing mutual communication through literature. Hermeneutic aspects of translation enhances understandability of the text in the target language created through hermeneutic analysis of the translator that was made after reading the original text in the source language. As whatever translated can’t be rendered without hermeneutic definition of the translator, all the occasions which need it distinctly and the ways how to apply it have been offered in the foregoing statements.